Alternative Dispute Resolution Through Mediation to Reduce Case Delays in Indonesian Courts - Ridwan (Journal of Law, Politic and Humanities, 2025)
The backlog of civil cases in court is a crucial issue in the Indonesian judicial system because it causes delays in dispute resolution, increases litigation costs, and reduces public trust in judicial institutions. In response to this situation, the Supreme Court has mandated mediation as the initial stage of civil case resolution through Supreme Court Regulation No. 1 of 2016. This policy reflects efforts to reform the judicial system to make it more efficient and oriented towards peaceful resolution. This study aims to evaluate the role of mediation in reducing case backlogs and increasing the efficiency of dispute resolution. In addition, this study compares the application of mediation in the General Court and the Religious Court. The method used is normative legal research with a legislative, conceptual, and philosophical approach. The results of the study show that mediation in the General Court tends to be formalistic, so its impact on reducing cases is still limited. In contrast, mediation in the Religious Court is more effective because it uses a persuasive, cultural, and religious approach. The efficiency of mediation should be interpreted not only as procedural acceleration but also as the realization of sustainable substantive justice.